2014
DOI: 10.1111/mec.12982
|View full text |Cite
|
Sign up to set email alerts
|

Compartment‐specific transcriptomics in a reef‐building coral exposed to elevated temperatures

Abstract: Although rising ocean temperatures threaten scleractinian corals and the reefs they construct, certain reef corals can acclimate to elevated temperatures to which they are rarely exposed in situ. Specimens of the model Indo-Pacific reef coral Pocillopora damicornis collected from upwelling reefs of Southern Taiwan were previously found to have survived a 36-week exposure to 30°C, a temperature they encounter infrequently and one that can elicit the breakdown of the coral–dinoflagellate (genus Symbiodinium) end… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
93
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 63 publications
(104 citation statements)
references
References 55 publications
7
93
0
1
Order By: Relevance
“…Our findings in the long-term response are similar to those of a previous investigation on the response of another adult scleractinian (Acropora millepora) to a 37-days exposure to low pH (elevated pCO 2 ) that reported absence of change in the expression of target genes associated with calcification and metabolism (Rocker et al, 2015). In agreement with this, previous studies suggest that temperature stress has a greater impact in gene expression of corals than pH (Mayfield et al, 2014;Davies et al, 2016), although resilience to stress conditions varies from one species to another (Loya et al, 2001), and even among populations of the same coral species occurring in habitats with different local conditions (Poli et al, 2017).…”
Section: Mild Stress Response Of the Coral To Low Phsupporting
confidence: 82%
“…Our findings in the long-term response are similar to those of a previous investigation on the response of another adult scleractinian (Acropora millepora) to a 37-days exposure to low pH (elevated pCO 2 ) that reported absence of change in the expression of target genes associated with calcification and metabolism (Rocker et al, 2015). In agreement with this, previous studies suggest that temperature stress has a greater impact in gene expression of corals than pH (Mayfield et al, 2014;Davies et al, 2016), although resilience to stress conditions varies from one species to another (Loya et al, 2001), and even among populations of the same coral species occurring in habitats with different local conditions (Poli et al, 2017).…”
Section: Mild Stress Response Of the Coral To Low Phsupporting
confidence: 82%
“…; Mayfield et al . ), genes and pathways involved in primary metabolism were dominant in the mRNA libraries. The dominant metabolic pathways in terms of the fraction of expressed sequences in the cDNA libraries were oxidative phosphorylation, photosynthesis and the TCA cycle.…”
Section: Discussionmentioning
confidence: 97%
“…Nothing is known about how the host regulates the supply of nitrate, nor its response to thermal stress. Previous studies that monitored the gene expression of nitrate-transporter 2 (nrt2) in Symbiodinium C under different thermal regimes and in different host species found that temperature had little impact on nrt2 expression (Mayfield et al, 2013a(Mayfield et al, ,b, 2014, but no studies have examined the activity of nitrate reductase of in hospite Symbiodinium under thermal stress.…”
Section: Discussionmentioning
confidence: 99%